JWST Reveals Powerful Feedback from Radio Jets in a Massive Galaxy at z = 4.1 - Roy, Namrata (2024)
We report observations of a powerful ionized gas outflow in the z = 4.1 luminous radio galaxy TNJ1338-1942hosting an obscured quasar using the Near Infrared Spectrograph (NIRSpec) on board JWST. We spatially resolve alarge-scale (∼15 kpc) outflow and measure outflow rates. The outflowing gas shows velocities exceeding 900 km s−1and broad line profiles with widths exceeding 1200 km s−1 located at an ∼10 kpc projected distance from the centralnucleus. The outflowing nebula spatially overlaps with the brightest radio lobe, indicating that the powerful radio jetsare responsible for the outflow kinematics. The gas is possibly ionized by the obscured quasar with a contributionfrom shocks induced by the jets. The mass outflow rate map shows that the region with the broadest line profilesexhibits the strongest outflow rates. The total mass outflow rate is ∼500 Me yr−1, and the mass loading factor is ∼1,indicating that a significant part of the gas is displaced outwards by the outflow. Our hypothesis is that theoverpressured shocked jet fluid expands laterally to create an expanding ellipsoidal “cocoon” that causes thesurrounding gas to accelerate outwards. The total kinetic energy injected by the radio jet is about 3 orders ofmagnitude larger than the energy in the outflowing ionized gas. This implies that kinetic energy must be transferredinefficiently from the jets to the gas. The bulk of the deposited energy possibly lies in the form of hot X-ray-emitting gas.